Bimetallic Au/Ag nanoparticle loading on PNIPAAm–VAA–CS8 thermoresponsive hydrogel surfaces using ss-DNA coupling, and their SERS efficiency. Issue 18 (5th March 2015) - Manikas, Anastasios C.; Papa, Antonio; Causa, Filippo; Romeo, Giovanni; Netti, Paolo A.
<x xml:space="preserve">Abstract</x> Thermoresponsive hydrogels can be efficiently used as templates for bimetallic noble metal surface loading for the fabrication of plasmonic surfaces with a wide range of applications.